Who is allowed to cooperate?: assessing the concept of membership of Interpol in light of the denial of participation of Taiwan - Calcara, Giulio (Democracy, governance, and law, 2025)
Purpose - The purpose of this chapter is to answer the following questions: What does the legal framework of Interpol say on matters of membership and about the mandate of the organization? Is Interpol keeping a neutral stance when applying its norms on membership, or is it caving to external political pressure? Methodology/approach - By assessing the stance of Interpol in excluding Taiwan, this chapter wishes to examine how and on what basis Interpol involves certain countries and territories in cooperation processes, while excluding others. To do so, this chapter analyzes the evolution of Interpol and its legal framework. Findings - There are several controversial aspects that can be highlighted concerning the exclusion of Taiwan from Interpol. The way Taiwan lost its membership in Interpol did not follow a pre-established constitutional procedure. Additionally, Interpol breached its own principle of neutrality by getting embroiled in a political dispute between China and Taiwan and by taking a side. Finally, the decision of Interpol of excluding Taiwan goes against its own constitutional aims. Originality/value - As political pressure is mounting at the international level for Taiwan to be included in Interpol at least as an observer, this chapter examines the legal framework governing the membership of the organization and its evolution. Thus, the chapter provides an objective legal analysis of the legal framework and identifies inconsistencies in the interpretation of the relevant norms. Crucially, the process of admitting and excluding members is strictly connected to the concept of democracy within international organization.